Evolution of nuclear auxin signaling: lessons from genetic studies with basal land plants. (7th August 2017) - Kato, Hirotaka; Nishihama, Ryuichi; Weijers, Dolf; Kohchi, Takayuki
Abstract : Genetic studies using model bryophytes have provided insights into the origin of the nuclear auxin pathway, its critical roles in plant development, and the increased complexity of the pathway during evolution. Abstract: Auxin plays critical roles in growth and development through the regulation of cell differentiation, cell expansion, and pattern formation. The auxin signal is mainly conveyed through a so-called nuclear auxin pathway involving the receptor TIR1/AFB, the transcriptional co-repressor AUX/IAA, and the transcription factor ARF with direct DNA-binding ability. Recent progress in sequence information and molecular genetics in basal plants has provided many insights into the evolutionary origin of the nuclear auxin pathway and its pleiotropic roles in land plant development. In this review, we summarize the latest knowledge of the nuclear auxin pathway gained from studies using basal plants, including charophycean green algae and two major model bryophytes, Marchantia polymorpha and Physcomitrella patens . In addition, we discuss the functional implication of the increase in genetic complexity of the nuclear auxin pathway during land plant evolution.